Ligand Mobility Regulates B Cell Receptor Clustering and Signaling Activation - Ketchum, Christina (The Biophysical Society, 2014)
Antigen binding to the B cell receptor (BCR) induces receptor clustering, cell spreading, and the formation of signaling microclusters, triggering B cell activation. Although the biochemical pathways governing early B cell signaling have been well studied, the role of the physical properties of antigens, such as antigen mobility, has not been fully examined. We study the interaction of B cells with BCR ligands coated on glass or tethered to planar lipid bilayer surfaces to investigate the differences in B cell response to immobile and mobile ligands. Using high-resolution total internal reflection fluorescence (TIRF) microscopy of live cells, we followed the movement and spatial organization of BCR clusters and the associated signaling. Although ligands on either surface were able to cross-link BCRs and induce clustering, B cells interacting with mobile ligands displayed greater signaling than those interacting with immobile ligands. Quantitative analysis revealed that mobile ligands enabled BCR clusters to move farther and merge more efficiently than immobile ligands. These differences in physical reorganization of receptor clusters were associated with differences in actin remodeling. Perturbation experiments revealed that a dynamic actin cytoskeleton actively reorganized receptor clusters. These results suggest that ligand mobility is an important parameter for regulating B cell signaling.